2009
DOI: 10.3130/jaabe.8.111
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Progress Management System for Steel Structure Construction

Abstract: Progress management is demanding because of the volume of information exchanged among the various parties involved in a project. In particular, steel structures for high-rise construction projects are among the major work items that require more intensive progress management. This research aims at developing a real-time progress management system through an automated module for scheduling estimates and using an RFID system for real-time construction progress. We propose a new technique that preconstruction eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In the monitoring and control system, the data from the system sensors are gathered using the integrated system protocol. Then, the real-time progress management system and the real-time visualization system [16], which are subsystems of the monitoring and control system, examine the construction progress and display its status in three dimensions.…”
Section: Case Descriptionmentioning
confidence: 99%
“…In the monitoring and control system, the data from the system sensors are gathered using the integrated system protocol. Then, the real-time progress management system and the real-time visualization system [16], which are subsystems of the monitoring and control system, examine the construction progress and display its status in three dimensions.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Their study was among the more sophisticated existing models that have been developed in an attempt to capture an accurate estimate of the progress at a site using material tracking technologies. They concluded that by using their proposed model, precise material quantities could be estimated and that material production, shopping, and onsite warehousing can be monitored in real-time (Kim et al, 2009). However, as with other studies that employed similar technologies, the most significant weakness of their proposed system remains the inability of the progress estimation model to measure other activities on construction projects.…”
Section: Data Fusion Models In Constructionmentioning
confidence: 99%
“…These models are incapable of dealing with many other activities on a site that are not directly associated with the movement of physical objects on a site, including some piping work, inspection, concrete curing, and interior finishing. Kim et al (2009) developed a system for the real-time progress management of steel structure construction projects by using an RFID system combined with a 4D model of the site. Their study was among the more sophisticated existing models that have been developed in an attempt to capture an accurate estimate of the progress at a site using material tracking technologies.…”
Section: Data Fusion Models In Constructionmentioning
confidence: 99%
“…Scheduling involves the important and complex process of coordinating activities in construction projects [5]. Progress management, as a critical task of project management [6], is one of the indicators to directly measure and evaluate the success or failure of the project. Therefore, fully and systematically identifying the risk factors of assembly construction schedule under the general contracting mode, clarifying the relationship between factors, and studying the transmission path of risk factors can effectively assist managers to make objective and scientific decisions and improve the management level of assembly construction schedule under general contracting mode.…”
Section: Introductionmentioning
confidence: 99%